Cattle microsatellite markers for amplification of polymorphic loci in Asian bovidae - Hanotte, Olivier H.; Verjee, Y.; Ochieng, J.; Rege, J.E.O. (Nepal Agricultural Research Council, 1999)
Microsatellite loci are the markers of choice in pedigree analysis and population genetics studies. In closely related species, cross-species amplification of loci may be used instead of the cloning of loci. Previously, successful cross-species amplification of a set of cattle (Bos taurus) microsatellite loci, isolated at the International Livestock Research Institute was observed in the swamp and river types of water buffalo (Bubalus bubalis) and Bali cattle (Bos banteng). Presently, the domestic Yak (Poephagus grunniens), and the Mithan (Bibos frontalis) were evaluated. Single locus amplification was obtained with 92% of the cattle primer pairs tested in Yak and with 80% of the primer pairs tested in Mithan (95% and 85°/a in Bali cattle and in water buffalo respectively). In the Yak and Mithan, 73% and 56%, respectively of those loci amplified were polymorphic (75% and 55% in Bali cattle and in water buffalo, respectively). Polymorphism at 8 cattle microsatellite loci, recommended for population genetic studies in cattle, was further investigated to determine their suitability in Asian bovidae. In general, microsatellite markers developed for cattle can be applied for conservation and population genetic studies of wild and domestic Asian bovidae. Nevertheless, a large number of loci need to be screened to determine a universal set of loci that will work in all Asian species.